Doing Pre-operative Investigations in Emergency Department; a Clinical Audit - Rafiq, Muhammad Salman; Rafiq, Maria; Rafiq, Muhammad Imran; Salman, Seema Gul; Hafeez, Sania (Archives of Academic Emergency Medicine, 2017)
Introduction: Pre-operative investigations for emergency surgical patients differ between centers. Following established guidelines can reduce unnecessary investigation, cost of treatment and hospital stay. The present audit was carried out to evaluate the condition of doing pre-operative investigations for three common surgical emergencies compared to National Institute for Health and Care Excellence (NICE) guidelines and local criteria. Methods: A retrospective clinical audit of acute-appendicitis, abscess and hernia patients admitted to the emergency department was carried out over a one-year period from July 2014 to July 2015. Data of laboratory investigations, their indication, cost and duration of hospital stay was collected and compared with NICE-guidelines. Results: A total of 201 patients were admitted to the emergency department during the audit period. These included 77(38.3%) cases of acute-appendicitis, 112 (55.7%) cases of abscesses, and 12 (6%) cases of hernia. Investigations not indicated by NICE-guidelines included 42 (20.9%) full blood counts, 29 (14.4%) random blood sugars, 26 (12.9%) urea tests, 4 (2%) chest x-rays, 13 (6.5%) electrocardiographs, and 58 (28.9%) urine analyses. These cost 25,675 Rupees (245.46 Dollars) in unnecessary investigation costs and 65.7 days of additional hospital stay. Conclusions: Unnecessary investigations for emergency surgical patients can be reduced by following NICE-guidelines. This will reduce workload on emergency services, treatment costs and the length of hospital stay.